Using microfluidic shear to assess transfusion requirements in trauma patients - Rachael A Callcut; James T Ross; Anamaria J Robles; Leslie H Vuoncino; Ashli C Barnes; Leonardo W Graeff; Taylor L Anway; Nico T Vincent; Nithya Tippireddy; Kimi M Tanaka; Randi J Mays (Trauma Surgery & Acute Care Open)
Background Viscoelastic assays have widely been used for evaluating coagulopathies but lack the addition of shear stress important to in vivo clot formation. Stasys technology subjects whole blood to shear forces over factor-coated surfaces. Microclot formation is analyzed to determine clot area (CA) and platelet contractile forces (PCFs). We hypothesize the CA and PCF from this novel assay will provide information that correlates with trauma-induced coagulopathy and transfusion requirements.Methods Blood samples were collected on adult trauma patients from a single-institution prospective cohort study of high-level activations. Patient and injury characteristics, transfusion data, and outcomes were collected. Thromboelastography, coagulation studies, and Stasys assays were run on paired samples collected at admission. Stasys CA and PCFs were quantified as area under the curve calculations and maximum values. Normal ranges for Stasys assays were determined using healthy donors. Data were compared using Kruskal-Wallis tests and simple linear regression.Results From March 2021 to January 2023, 108 samples were obtained. Median age was 37.5 (IQR 27.5–52) years; patients were 77% male. 71% suffered blunt trauma, 26% had an Injury Severity Score of ≥25. An elevated international normalized ratio significantly correlated with decreased cumulative PCF (p=0.05), maximum PCF (p=0.05) and CA (p=0.02). Lower cumulative PCF significantly correlated with transfusion of any products at 6 and 24 hours (p=0.04 and p=0.05) as well as packed red blood cells (pRBCs) at 6 and 24 hours (p=0.04 and p=0.03). A decreased maximum PCF showed significant correlation with receiving any transfusion at 6 (p=0.04) and 24 hours (p=0.02) as well as transfusion of pRBCs, fresh frozen plasma, and platelets in the first 6 hours (p=0.03, p=0.03, p=0.03, respectively).Conclusions Assessing coagulopathy in real time remains challenging in trauma patients. In this pilot study, we demonstrated that microfluidic approaches incorporating shear stress could predict transfusion requirements at time of admission as well as requirements in the first 24 hours.Level of evidence Level II.